Exploring the pharmacological mechanism of Tongluo Qingnao formula in treating acute ischemic stroke: A combined approach of network pharmacology, molecular docking and experimental evidences - Feng Li; Yilei Dong; Guangrui Wang; Zishan Huang; Wenting Song; Xiaoyu Zheng; Peng Zhang; Mingjiang Yao (Pharmacological Research - Modern Chinese Medicine, 2024)
Introduction: Tongluo Qingnao (TLQN) Formula is a patent Traditional Chinese Medicine injection designed for the treatment of Acute Ischemic Stroke (AIS) and associated complications. Previous researches had shown promising potential of TLQN in treating ischemic brain edema. This study aimed to reveal specific mechanisms of TLQN in treating AIS by bioinformatics analysis and following confirmatory experiments. Methods: HPLC was used to analyze the active ingredients of TLQN. Network Pharmacology and Molecular Docking were introduced to screen treatment targets and pathways. And then middle cerebral artery occlusion and reperfusion (MCAO/R) model was established in rats to verify the therapeutic effect of TLQN in neurological deficit score, cerebral infarction size, HE staining, TUNEL staining, and proteins expression related to inflammation, apoptosis and the PI3K-AKT signaling pathway. Results: Seven main active ingredients were contained in TLQN. Network pharmacology identified IL-6 and IL-1β as the key targets, and PI3K-AKT as the critical pathway. Molecular Docking analysis indicated that the constituents of TLQN demonstrated a high affinity for crucial targets. TLQN could significantly reduce neurological deficits, pathological lesions and apoptosis caused by AIS. Western blotting results indicated that TLQN can activate the PI3K-AKT signaling pathway, inhibit the expression of pro-apoptotic proteins bax, Caspase-3 and inflammatory factors IL-6, IL-1β. Discussion: TLQN has a therapeutic effect on AIS, and these results highlight the therapeutic effects of TLQN on AIS by activating PI3K-AKT signaling pathway to inhibit inflammation and apoptosis.